The prevalence of bleeding after percutaneous coronary interventions: Systematic review and meta-analysis - Shohaimi, Shamarina; Moghadam, Reza Heidary; Mohammadi, Aida; Salari, Nader; Mohammadi, Masoud; Ahmed, Arkan (Elsevier, 2024)
Background Bleeding is a common complication associated with percutaneous coronary intervention (PCI). The aim of this study was to determine the prevalence of bleeding after PCI through a systematic review and meta-analysis. Methods The systematic review and meta-analysis covered the period from 1989 to 2023. Multiple databases, including Embase, PubMed, Scopus, Web of Sciences (WoS), MagIran, Scientific Information Database (SID), and Google Scholar, were searched using validated keywords with MeSH and Emtree. The I2 index was used to check for heterogeneity among studies. Results The review of 8 studies, with a sample size of 397,298 participants, showed high heterogeneity (I2: 97.8 %). Therefore, the random effects method was used to analyze the results. The prevalence of bleeding after intervention in percutaneous coronary arteries was reported to be 4.4 % (95%CI: 2–9.1). Conclusion This meta-analysis showed a significant prevalence of bleeding after PCI, highlighting the need for health policymakers to pay more attention to the complications associated with PCI. Interventional cardiologists should consider the effective factors in these bleeding and how to treat and control them due to the importance of this complication.